The Impact of Solidarity and Teamwork Among Medical Staff on Surgical Outcomes: A Systematic Review - Altarooti, Hameedah Mansoor; AlHunaidi, Ayat Ahmed; Al Hauinaidi, Zainab Ahmad; Albishi, Haya Omair Mefareh; Al- jrad, Fawzia Ibrahim; Aldoosry, Samaher joher; subaiti, Sakinah Hussain; Alsadah, Majedah Alawi; Alqassab, Hanadi Ali Abdulla; Albeesh, Hajer Ali (Journal of Ecohumanism, 2024)
Background: Surgical operations require seamless collaboration and coordination among medical staff to ensure optimal patient outcomes. Solidarity and teamwork play a pivotal role in minimizing errors, improving efficiency, and enhancing overall surgical performance. Despite growing awareness of their importance, the specific impacts of these factors on surgical outcomes remain underexplored. Objectives: This systematic review aims to assess the influence of solidarity and teamwork among medical staff on surgical outcomes, including patient safety, procedure success rates, and postoperative recovery. Methods: A comprehensive literature search was conducted across databases such as PubMed, Cochrane Library, and Scopus. Studies published from 2016 onwards, focusing on teamwork in surgical environments, were included. Articles were screened and analyzed based on predefined criteria, with thematic and quantitative data synthesized for key insights. Results: The review included 25 studies from various regions, emphasizing the critical role of effective communication, mutual respect, and leadership in fostering collaboration. Key findings indicated that teams with high levels of solidarity experienced reduced surgical errors (by up to 30%), shorter procedure times, and improved patient recovery rates. Training programs aimed at enhancing teamwork were also associated with sustained improvements in outcomes. Conclusion: Solidarity and teamwork among medical staff are essential for achieving superior surgical outcomes. Healthcare organizations should prioritize team-building initiatives, effective communication training, and leadership development to foster a collaborative surgical environment. Future research should explore cultural and institutional factors influencing teamwork in surgical settings